A tale of two parks: Tibetan youths' preferences for tourism community futures. Issue 4 (8th August 2017) - Wu, Mao-Ying; Pearce, Philip L.
Abstract : This study explores young hosts' identification of tourism resources and their perceptions of different tourism site management styles in a suburban village in Lhasa, Tibet. Two tourism parks with different management styles co-exist in the same village. One is collectively owned and managed by the community and the other is developed and managed by an outside company. Compared with previous tourism community research, this empirical study has four notable features: it focuses on a non-Western, emerging tourism community; compares responses to two different development approaches within a community; targets the emic views of the young local citizens; and connects the present with the future. A combination of research methods, including key informant interviews, photo-elicitation interviews, and a questionnaire-based survey were used in sequence. The study suggests that the Tibetan young hosts have clear views about tourism, the future, and their local resources. They strongly preferred the community-based style for the future, and their preferences extended to the kinds of tourists who visited the community-based property. The study adds empirical weight to the voices of those researchers who call for strong community control over local tourism resources as well as suggesting the benefits this approach may deliver.